Some data on North German stops and affricates - Fischer-Jørgensen, Eli (Annual Report of the Institute of Phonetics University of Copenhagen, 1976)
The present paper presents some data on voicing (3.1), duration (3.2), intra-oral air pressure (3.3), airflow (3.4), subglottal pressure (3.5), and lip pressure (3.6) of German stops and affricates. On the basis of these data the last section discusses some more general problems, viz. the features distinguishing ptk and bdg (4.1), the reduction of aspiration after s (4.2), the distinction between stops and affricates (4.3), differences due to place of articulation (4.4), "heightened subglottal pressure" (4.5), and the relation between air pressure and airflow (4.6).